Biocomputing 2017 2016
DOI: 10.1142/9789813207813_0009
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis for Lung Adenocarcinoma Predicts Morphological Features Associated With Genetic Variations

Abstract: Lung cancer is one of the most deadly cancers and lung adenocarcinoma (LUAD) is the most common histological type of lung cancer. However, LUAD is highly heterogeneous due to genetic difference as well as phenotypic differences such as cellular and tissue morphology. In this paper, we systematically examine the relationships between histological features and gene transcription. Specifically, we calculated 283 morphological features from histology images for 201 LUAD patients from TCGA project and identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…An important computational issue is how to effectively integrate the omics data with digitized pathology images for biomedical research. Multiple statistical and machine learning methods have been applied for this purpose including consensus clustering [ 250 ], linear classifier [ 251 ], LASSO regression modeling [ 252 ], and deep learning [ 253 ]. These methods have been applied to studies on cancers, including breast [ 250 ], lung [ 252 ], and colorectal [ 253 ].…”
Section: Integrative Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important computational issue is how to effectively integrate the omics data with digitized pathology images for biomedical research. Multiple statistical and machine learning methods have been applied for this purpose including consensus clustering [ 250 ], linear classifier [ 251 ], LASSO regression modeling [ 252 ], and deep learning [ 253 ]. These methods have been applied to studies on cancers, including breast [ 250 ], lung [ 252 ], and colorectal [ 253 ].…”
Section: Integrative Analyticsmentioning
confidence: 99%
“…Multiple statistical and machine learning methods have been applied for this purpose including consensus clustering [ 250 ], linear classifier [ 251 ], LASSO regression modeling [ 252 ], and deep learning [ 253 ]. These methods have been applied to studies on cancers, including breast [ 250 ], lung [ 252 ], and colorectal [ 253 ]. The studies not only demonstrated that integration of morphological features extracted from digitized pathology images and -omics data can improve the accuracy of prognosis but also provided insights on the molecular basis of cancer cell and tissue organizations.…”
Section: Integrative Analyticsmentioning
confidence: 99%
“… 1 , 2 The development of LUAD is a complicated, multiple-stage process, and various factors including genetic mutations, cigarette smoking, and environment toxins contribute to the tumorigenesis. 3–5 The advances in diagnosis and therapy greatly improve the outcome of LUAD patients. 6 However, the prognosis of LUAD patients remains poor due to the tumor metastasis and recurrence, while the 5-year survival rate of LUAD is only around 15%.…”
Section: Introductionmentioning
confidence: 99%
“…Since cancer can be characterized by tissue and cellular morphological features from histopathological images and by molecular features from molecular omics data, an interesting scientific question arises — will tumor genetic changes be reflected at the tissue morphological level? Integrative analysis of multimodal data has been previously carried out in cancers such as glioblastoma ( 32 ), kidney cancer ( 3 , 6 ), lung cancer ( 33 ), breast cancer ( 34 , 35 ), and ovarian cancer ( 36 ). Using glioblastomas as an example, Cooper et al.…”
Section: Introductionmentioning
confidence: 99%